A globally relevant change taxonomy and evidence‐based change framework for land monitoring. (1st September 2022) - Lucas, Richard M.; German, Sophia; Metternicht, Graciela; Schmidt, Rebecca K.; Owers, Christopher J.; Prober, Suzanne M.; Richards, Anna E.; Tetreault‐Campbell, Sally; Williams, Kristen J.; Mueller, Norman; Tissott, Belle; Chua, Sean M. T.; et al.
Abstract: A globally relevant and standardized taxonomy and framework for consistently describing land cover change based on evidence is presented, which makes use of structured land cover taxonomies and is underpinned by the Driver‐Pressure‐State‐Impact‐Response (DPSIR) framework. The Global Change Taxonomy currently lists 246 classes based on the notation 'impact (pressure)', with this encompassing the consequence of observed change and associated reason(s), and uses scale‐independent terms that factor in time. Evidence for different impacts is gathered through temporal comparison (e.g., days, decades apart) of land cover classes constructed and described from Environmental Descriptors (EDs; state indicators) with pre‐defined measurement units (e.g., m, %) or categories (e.g., species type). Evidence for pressures, whether abiotic, biotic or human‐influenced, is similarly accumulated, but EDs often differ from those used to determine impacts. Each impact and pressure term is defined separately, allowing flexible combination into 'impact (pressure)' categories, and all are listed in an openly accessible glossary to ensure consistent use and common understanding. The taxonomy and framework are globally relevant and can reference EDs quantified on the ground, retrieved/classified remotely (from ground‐based, airborne or spaceborne sensors) or predicted through modelling. By providing capacity to more consistently describe change processes—including land degradation, desertification and ecosystem restoration—the overall framework addresses a wide and diverse range of local to international needs including those relevant to policy, socioeconomics and land management. Actions in response to impacts and pressures and monitoring towards targets are also supported to assist future planning, including impact mitigation actions. Abstract : The globally relevant and standardized change taxonomy and framework provides consistent descriptions of land cover dynamics, is underpinned by the Driver‐Pressure‐State‐Impact‐Response (DPSIR) framework and utilizes structured land cover taxonomies. The taxonomy defines and describes 246 change categories that use the notation 'impacts (pressures)'. The taxonomy and evidence‐based change framework are scalable in space and time and can be applied to describe past and future (predicted or planned) changes, including at the ground, from Earth observations and through predictive models.